The Development of Sharia Courts in Aceh, Indonesia: A Social and Historical Perspective on Islamic Law - Nurdin, Abidin; Ridhwan, Ridhwan; Zulkarnaen, Teuku; Halimang, St; Samad, Fauzan (El-Usrah: Jurnal Hukum Keluarga, 2026)
If the Sharia Court in Aceh is examined from a historical perspective, its institutional roots can be traced to the office of the qadhi (Islamic judge) during the era of the Islamic sultanates. This historical fact influenced the colonial period, independence, the New Order, and the Reformation era. This study aims to examine the development of the Sharia Court from the kingdom era to the Reformation era using an Islamic legal social history approach. This study employs empirical legal methods, analyzed using Islamic legal social history theory. Data were collected through document studies and interviews. The documents analyzed included laws, regulations, books, journal articles, and court decisions. The informants interviewed included academics, judges, and non-Muslim members of the public. The study finds that the development of the Sharia Court in Aceh has experienced significant fluctuations from the sultanate period to the reform era. During the sultanate era, Islamic judicial institutions flourished, with courts led by qadhi who functioned as both legal authorities and moral arbiters within society. In the colonial period, particularly under Dutch and Japanese rule, Islamic courts were progressively marginalized, resulting in legal pluralism marked by tensions among Islamic law, customary law (adat), and Western legal systems. In the post-independence period, religious courts gradually gained formal recognition within the national legal system, including the incorporation of women as judges, reflecting increasing institutionalization and gender inclusivity. During the reform era, the Sharia Court underwent a process of revitalization, particularly following the implementation of special autonomy in Aceh and the formal introduction of the Islamic law within the regional legal system.